Policing during the COVID-19 pandemic: a global perspective - Kutnjak Ivković, Sanja; Kotlaja, Marijana; Maskáli, Jon; Neyroud, Peter (Routledge, 2024)
"Providing a global perspective on police adaptations to the COVID-19 pandemic, Policing During the COVID-19 Pandemic explores the extent of police organizational and operational changes in a number of countries as diverse as Brazil, China, South Africa, South Korea, the Philippines, Russia, the United Kingdom, and the United States"--